Madrasah Management Strategies for Supporting Transfer Student Adaptation: A Case Study in an Indonesian Islamic Elementary School - Miftahul Abidin; Yulia Tri Samiha; Padli Padli; Saipul Annur (Ali Institute of Research and Publication, 2026)
This study aims to analyze the madrasah management strategies in overcoming the adaptation challenges of transfer students at MI Hijriyah 2 Palembang, to describe the supporting and inhibiting factors of the adaptation process, and to explain the roles of madrasah leadership, teachers, and the school environment in accelerating the students' academic, social, and religious integration. School transfers cause psychological stress, differences in learning cultures, and academic ability gaps that require systematic managerial handling. This study uses a descriptive qualitative approach with a case study design. Data were obtained through observation, in-depth interviews, and documentation involving the madrasah principal, homeroom teachers, religious education teachers, and transfer students. Data analysis utilized the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing and verification. Data validity was tested through source and technique triangulation. The results indicate that the adaptation management strategies for transfer students at MI Hijriyah 2 Palembang are implemented through orientation programs, differentiated learning, individual mentoring, peer support, religious habituation, and consistent institutional coordination. These strategies are able to create a sense of psychological security, increase academic participation, strengthen social integration, and foster the students' religious discipline. The main supporting factors include adaptive madrasah leadership, an inclusive school culture, humanistic teacher involvement, and a safe learning environment. Inhibiting factors encompass differences in students' initial abilities, emotional anxiety, limited teacher mentoring time, and adjustments to the school's religious culture. Overall, structured adaptation management has proven effective in facilitating the transformation of transfer students from a phase of alienation to active involvement in madrasah life